Ceramic high-rate timing RPCs - Lopes, L. (2006)
Following some previous work, we report here considerable improvements on the counting rate capability of timing RPCs by the use of ceramic electrodes with a resistivity of 109 [Omega][dot operator]cm. The X-ray sensitivity of the detector depends linearly on the counting rate with a slope of 9% per 100 kHz/cm2, free from charge depletion effects, while keeping a timing accuracy, measured with 511 keV synchronous photon pairs, around 90 ps [sigma] up to 75 kHz/cm2.